2021
DOI: 10.1186/s12935-020-01720-y
|View full text |Cite
|
Sign up to set email alerts
|

Verteporfin disrupts multiple steps of autophagy and regulates p53 to sensitize osteosarcoma cells

Abstract: Background Osteosarcoma (OS) is a malignant tumor of the bone mostly observed in children and adolescents. The current treatment approach includes neoadjuvant and adjuvant chemotherapy; however, drug resistance often hinders therapy in OS patients. Also, the post-relapse survival of OS patients is as low as 20%. We therefore planned to understand the molecular cause for its poor prognosis and design an appropriate therapeutic strategy to combat the disease. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…Post multiple PBS washes, cells were blocked with 2.5% bovine serum albumin (BSA) blocking solution for 1 h. The cells were then incubated overnight with primary antibody (1:500 dilution in 2.5% BSA) at 4°C, followed by washing twice with PBS, and then incubated with TRITC-conjugated secondary antibody (1:1,000 in 2.5% BSA) for 1 h. Coverslips were mounted on slides using antifade DAPI and imaged under a fluorescent microscope (Zeiss, Axio Scope A1, or Axio Observer.Z1/7). Images were analyzed using the Zen 3.2 (blue edition) software ( 48 ).…”
Section: Methodsmentioning
confidence: 99%
“…Post multiple PBS washes, cells were blocked with 2.5% bovine serum albumin (BSA) blocking solution for 1 h. The cells were then incubated overnight with primary antibody (1:500 dilution in 2.5% BSA) at 4°C, followed by washing twice with PBS, and then incubated with TRITC-conjugated secondary antibody (1:1,000 in 2.5% BSA) for 1 h. Coverslips were mounted on slides using antifade DAPI and imaged under a fluorescent microscope (Zeiss, Axio Scope A1, or Axio Observer.Z1/7). Images were analyzed using the Zen 3.2 (blue edition) software ( 48 ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, metformin inhibited matrix metalloproteinase-9 activation, decreased endogenous insulin resistance, suppressed HER2 (erbB-2) oncoprotein overexpression, improved cancer patient's survival in type 2 diabetes, and blocked migration as well as invasion of cancer cells (Sui et al, 2011). Recently, Saini et al found that verteporfin, known as autophagy inhibitory and proteotoxic functions, disrupts multiple steps of autophagy in addition to regulate p53 to sensitize osteosarcoma of human osteosarcoma cells-HOS (R156P mutant P53) (Saini et al, 2021). microRNA, miR-26b, improves the sensitivity of hepatocellular carcinoma to doxorubicin by USP9X-dependent degradation of p53 as well as autophagy regulation (Chen et al, 2021).…”
Section: Synthetic Drug Targeting P53-mediated Autophagy Modulation In Cancermentioning
confidence: 99%
“…To explore the role of p62 in proteaphagy, verteporfin (VTP, a clinical-grade small molecule inhibitor of this autophagy receptor) was employed [ 30 , 31 ]. Unlike BafA, VTP inhibits autophagy at an early stage by aggregation of p62 and reduces autophagosome accumulation such that it can be assessed by a reduction of the autophagy marker LC3B [ 32 , 33 ]. Whereas the levels of LC3B and its lipidated form decreased, high-molecular weight aggregates of p62 accumulated after VTP treatment in both Z-138 and ZBR cells.…”
Section: Resultsmentioning
confidence: 99%